TRANSFER OF LAND RIGHTS (SALE AND PURCHASE ACT WITH SALE AND PURCHASE BINDING AGREEMENT) STUDY AT THE NOTARY & PPAT OFFICE BUDI ARIPIN S.SOS, S.H, M.KN. - Zelfi Ghaffar Aufiya; Mujadidi Al Falahi; Ade Samsul; Gevira Izatun Nisa; Angel Virgi Azzahra; Aufa Aqlani Alparabi (Ann Publisher, 2025)
Abstract: Background. The Sale and Purchase Binding Agreement (PPJB) serves as a binding preliminary agreement between the seller and the buyer before the Sale and Purchase Act (AJB) is drafted by the Land Deed Making Office (PPAT). Aims. Transferring land rights requires registration at the National Land Agency (BPN) to ensure legal certainty. Problems can arise if the fulfillment of rights and obligations does not accompany fulfilling the rights contained in the PPJB. This can result in the inability to make an AJB by PPAT to change the certificate's name to the land office where the object is located. Methods. The juridical normative method used requires both primary and secondary data. Primary data is obtained from the study location, the Notary Office & PPAT Budi Aripin, S.Sos, S.H, M.Kn. In contrast, secondary data is obtained from literature. Result. The results of his research show that the function of the deed made by the Notary is to provide legal certainty and guarantee the right to land ownership, as well as evidence that legal acts have been carried out, and the factors that hinder the transfer of land rights through sale and purchase. Conclusion. A binding sale and purchase agreement is a form of preliminary agreement. Therefore, it can be used as a basis for making an AJB and serves as a document or evidence to complete the registration requirements for the transfer of land rights due to the sale and purchase transaction. Implementation. However, implementing all the conditions agreed to in this agreement can take quite a long time. This can prevent potential sellers from signing the AJB.